Prevalence of Multidrug-Resistant and Extended-spectrum Betalactamase Producing Bacterial Isolates from Infected Wounds of patients in Kathmandu Model Hospital - Adhikari, Kabita; Basnyat, Shaila; Shrestha, Basudha (Nepal Journal of Science and Technology, 2020)
The wound is an injury to living tissues caused by a cut, puncture, bite, blow, or other impacts. An infection is caused when germs enter wounds. This study was designed to isolate and identify the causative agents of wound infections and their antibiotic susceptibility pattern. A total of 339 samples were collected from January to June 2016 from Kathmandu Model Hospital, Kathmandu. Samples were inoculated on the Blood Agar and MacConkey agar plates were incubated at 37 °C for 24 hours. After incubation, all isolates were identified by using gram stain and biochemical methods. Antibiotic susceptibility tests were performed on Mueller Hinton agar plate by Kirby Bauer Disk Diffusion Technique. During the study period, altogether, 339 specimens were collected and processed as per the standard microbiological protocol. The overall prevalence of wound infection was 56.9%. Among 244 bacterial isolates, Escherichiacoli (24.2%) was most predominant bacteria followed by Staphylococcus aureus (19.7%), Coagulase-negative Staphylococcus (17.6%), Klebsiella pneumoniae (10.7%), Pseudomonas aeruginosa (8.6%), Acinetobacter spp (5.7%), Citrobacter freundii (4.9%) Proteus mirabilis (3.3%), Streptococcus viridans (2.0%), Klebsiella oxytoca (0.8%), Proteus vulgaris (0.4%), Serratia marcescens (0.4%), Enterobacter aerogens (1.2%), Enterobacter faecalis (0.4%). The most effective drug for Gram-negative bacteria and Gram-positive bacteria were amikacin and chloramphenicol, respectively. A total of Gram-negative bacteria, 77.55% were multidrug-resistant. The total Gram-negative bacteria most ESBL producers were E. coli (82.9%). We found S. aureus 33.3% of isolates were resistant to cefoxitin which indicates the increasing rate of Methicillin-resistant S. aureus (MRSA) in wound infection.